(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This comprehensive literature review explores the dynamic landscape of nutrition influencer marketing, focusing on the evolving role of influencers in shaping consumer choices and wellness trends. Nutrition influencers, distinct from traditional experts, leverage social media to amass substantial followings, influencing food choices and lifestyle preferences. The review critically examines the conceptual underpinnings of nutrition influencer marketing, highlighting the limited academic inquiry in this rapidly expanding field